Nativized Ways of Using English Language in Public Signage: Exploring Lahore’s Linguistic Landscape - Yasir, Hafiz Syed M.; Khalid, Amina (Pakistan Languages and Humanities Review, 2024)
The purpose of this study is to highlight the linguistic landscape of Lahore (Punjab, Pakistan) by covering the discussion regarding the ways of using English language as nativized and localized version. This study is based on different trends of public of using English language in different ways to advertise their agencies (shop names, business centers etc.). To collect the data, three areas of Lahore were selected based on the convenience sampling technique (as data was homogenous across the city) i.e. Thoker Niaz Baig, Township, Anarkali. Purposive sampling was under consideration as only text-based displays were considered to collect the data which showed the use of English language in them. 60 pictures were taken with the help of a digital camera and were made limited to 52 after the refining process. Blurred and repeated photographs were excluded. Analytical parameters of Cenoz & Gorter (2006) were considered to analyze the data. Some guidance in analysis was taken from the study of Landry & Bourhis (1997) regarding the unit of analysis. Only the text of different signboards was considered to analyze. Results revealed the presence of different nativized ways of using English language i.e. direct use of English, Roman English, transliteration and code-mixed English. The study reveals the patterns which are adopted by the public to use English language to display and advertise their businesses and commercials (printed). For future recommendations, linguistic landscape can be studied from the viewpoint of bi/multilingualism, language policy making, cultural integration and to transpire the novice linguistic patterns.